On the Consistency and Efficiency of Central Plans - Montias, J. M. (Review of Economic Studies, 1962)
Journal Article On the Consistency and Efficiency of Central Plans Get access J. M. Montias J. M. Montias New Haven Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 4, October 1962, Pages 280–290, https://doi.org/10.2307/2296304 Published: 01 October 1962